The practical guide to managing event venues - Berners, Philip (Routledge, 2019)
"This is a short, accessible and practical guide to running venues which are in the business of hosting events. Using honest guidance peppered with the author's real-life situational anecdotes to contextualise the topics, the book is logically structured around the key stages of event management - pre-event, onsite and post-event. Topics covered include developing the client relationship, marketing, financial accountability, risk, interdepartmental communication, onsite procedures and post-event evaluation. This is a fundamental resource for all events management and hospitality students. It is also a book for anybody who manages a venue or is a venue event manager. The Practical Guide to Managing Event Venues makes the business of venue management appealing, understandable and achievable"-- Provided by publisher.